Empirical Study: Relationship between Self Efficacy and Academic Performance - Chanana, Meenakshi (International Research Journal of Management, IT & Social Sciences, 2016)
This paper examines the relationship between the self-efficacy and academic performance in Graduation level students. The data was collected from 130 students (42 females and 88 males) selected from different semesters of undergraduate studies. To analyze data correlation and t-test analysis was used. The results of the study showed that there is a significant relationship between self-efficacy and academic performance of the students. In addition, we found that there is no significant relationship between self-efficacy and academic performance among students varied by age or course. From the findings, it was recommended that teachers, Counsellors, and educators should give continuous advice and develop techniques that help lower anxiety and reduce stress, to increase studentâs self-efficacy.